Hybrid Mobile Executive Information (m-EIS) System Using Quasar Framework for Indonesia Financial Service Authority - Dina Fitria Murad; Wirianto Widjaya; Dwi Rahmania Noviani; Nur Fitriyyah; Liany Minarni Saputri (Journal of Information Systems Engineering and Business Intelligence, 2019)
Background: Given the digital transformation in currently emerging digital era in Financial Service Industry; marked by the rise of Fintech; Financial Service Authority (FSA) is challenged to mitigate new type of risks that are introduced by it. As first step, Indonesia FSA seeks for an effective and efficient way to present up-to-date Strategic Information to its Top Executive Leaders to enable informed strategic decision making.Objective: This study aimed to find the solution to provide information strategic information to Indonesia FSA executives at any-time any-where. The researchers hypothesize that mobile Executive Information System could effectively serve the purpose.Methods: The research activities are laid out based on the Unified Process (UP) Methodology and use Unified Modelling Language (UML) diagrams to communicate the design. At the end of the study, a survey-based on TAM2 is conducted to confirm the study result. The survey is tested to measure its validity, reliability and correlation analysis using SPSS.Results: The study produce mobile executive information system (m-EIS) geared with the latest UI technology framework; Quasar; and microservice pattern. The m-EIS is deployed and implemented. The survey result shows the overall users’ acceptance of the implementation.Conclusion: The study recommends the further enhancement of m-EIS and highlights limitation of the current study for which future study could address and improve.Keywords:Executive Information System, Financial Service Authority, Financial Service Industry, Hybrid Mobile Application, Unified Modelling Language, Unified Process